Synthesis of 4H-chromenes promoted by NbCl5 through multicomponent reaction - Oshiro, Paula Beatriz [UNESP]; Da Silva Gomes Lima, Paula Souza [UNESP]; De Menezes, Manoel Lima [UNESP]; Da Silva-Filho, Luiz Carlos [UNESP] (Elsevier, 2015)
Abstract Multicomponent reactions between phenols, β-ketoesters, and benzaldehydes for the synthesis of 4H-chromenes derivatives promoted by niobium pentachloride (NbCl5) were carried out, providing good yields and reasonable reaction times under mild reaction conditions.
Keywords: Chromene derivatives; Lewis acid; Multicomponent reaction; Niobium pentachloride